Correlation between Superoxide Dismutase 1 and 2 Polymorphisms in Asthma Patients - Walaa Najah Majid; Layla Mohsen Mehdi (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was designed to investigate the effectof polymorphisms of Superoxide desmutase1 and 2genesand how they contribute to the risk of developing asthma.A total 120 were involved in the present study anddivided into four groups and each group included 30 samples. First group was consisted 30 asthma malepatients with waterpipe smoking and second group was also 30 asthma male patients with no smoking,third group was control (no disease) with waterpipe smoking and the fourth group was control group(no disease and without waterpipe smoking).Blood samples were collected from Muthanna hospital andprivate laboratories from the periodmid-August to the mid-November 2020. To study the polymorphismphenomenon of SOD1 and SOD2 genes were assessed using RFLP- polymerase chain reaction (RFLPPCR)technique. This study confirmed that the phenomenon of polymorphism of the SOD1 genewas notassociated with the group of patients infected with asthma comparedto control group. This study conductedthat the phenomenon of polymorphism of the SOD2 geneis not associated with the group of patients infectedwith asthmacomparedto control group in presence and absence of waterpipe smoking.